2017
DOI: 10.1007/s00018-017-2498-9
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of systemic DHA synthesis affects macrophage plasticity and polarization: implications for DHA supplementation during inflammation

Abstract: Docosahexaenoic acid (DHA) is an omega-3 fatty acid obtained from the diet or synthesized from alpha-linolenic acid through the action of fatty acid elongases (ELOVL) and desaturases. DHA plays important roles in the central nervous system as well as in peripheral organs and is the precursor of several molecules that regulate resolution of inflammation. In the present study, we questioned whether impaired synthesis of DHA affected macrophage plasticity and polarization both in vitro and in vivo models. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 34 publications
3
54
0
1
Order By: Relevance
“…Thus, macrophage function and phenotype are highly dependent on their microenvironment [40]. Lipids (cellular or dietary) and alterations in lipid metabolism have long been identified as regulators of immune cell function and macrophage polarization [27,[41][42][43][44]. Consistent with previous reports, our data demonstrate that PA and Cer attenuate the M2-phenotype in macrophages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, macrophage function and phenotype are highly dependent on their microenvironment [40]. Lipids (cellular or dietary) and alterations in lipid metabolism have long been identified as regulators of immune cell function and macrophage polarization [27,[41][42][43][44]. Consistent with previous reports, our data demonstrate that PA and Cer attenuate the M2-phenotype in macrophages.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, reprogramming M2 TAMs towards the immunogenic M1 phenotype in vivo to block tumor progression could be a promising strategy for the treatment of cancers. In this context, several studies have demonstrated the potential of lipids to modulate macrophage function and phenotype [26,27]. Palmitic acid (PA), a saturated fatty acid, was shown to induce an inflammatory response in macrophages by amplifying LPSmediated signaling via TLR4 [28,29], potentially mediated by NF-κB activation [30].…”
mentioning
confidence: 99%
“…In particular, docosahexaenoic acid (DHA) promoted antiinflammatory M2 function. Impairment of the biosynthetic pathway of DHA increased the level of proinflammatory M1 phenotype (16,17). In addition, metabolites of DHA, i.e., specialized proresolving lipid mediators (SPMs) including resolvins, protectins, and maresins (MaR), are involved in the resolution of acute inflammation, which is an important step for orchestrating the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…45 Our group has previously shown that these mice are characterized by severely reduced DHA levels in testis, serum, liver, mammary gland and white adipose tissue 6,26,44 as well as by a pro-inflammatory status of innate immune cells. 25 In the present work, we collected the unprecedented evidence of acyl-CoA levels in brain by targeted lipidomics and we demonstrated that Elovl2-mediated endogenous DHA synthesis plays a role in the expression of several brain plasticity and inflammatory markers. Although, to date, it is unclear why brain phospholipids are specifically enriched in DHA and low in DPA and EPA, the fact that DHA enrichment is conserved across species 46,47 suggests that there is a highly specific requirement for this essential fatty acid in neuronal membranes.…”
Section: Discussionmentioning
confidence: 90%
“…23,24 Indeed, we have recently shown that the impairment of systemic DHA synthesis in Elovl2 −/− mice, delineates an immunophenotypical alteration of M1/M2 macrophages, with M1 being more pro-inflammatory and M2 less protective, supporting the view that DHA has a relevant role in controlling inflammatory responses. 25 Given that DHA plays a key role in CNS function and plasticity and is a potent anti-inflammatory mediator, we sought to systematically investigate whether Elovl2 −/− mice, characterized by a systemic impairment of endogenous DHA synthesis, displayed neuronal plasticity dysfunctions and brain inflammation and whether such alterations could be restored upon DHA supplementation.…”
Section: Introductionmentioning
confidence: 99%